MOTIF CERITA RAKYAT SEBAGAI SARANA PENJAGA INTEGRITAS SOSIAL MASYARAKAT ASEAN - Lilik Wahyuni (Waskita: Jurnal Pendidikan Nilai dan Pembangunan Karakter, 2019)
Folklore is a traditional story to convey the noble values of a region to the future generations which are delivered using spoken language. The focus of this study are (1) the motifs and variations of Malin Kundang folklore in various ASEAN countries, (2) the function of folklore as the guardian of ASEAN social integrity, and (3) educational value of folklore as the guardian of ASEAN social integrity. This study used a qualitative approach with ethnography of communication design. The main data in this study are the words and actions which are delivered by the speakers used in folklore. The data collection method used in this research is focused observation. The data were analyzed by sorting, selecting, and interpreting the data. Based on the results of data analysis can be concluded that (1) the motif of "Malin Kundang" and its versions are (a) a teenager from a poor family, (b) the teenager ventured into the land, (c) he /she became successful and married with the child of a rich merchant, (d) the young merchant traded to his/her hometown, (e) the mother got to hear the return of herchild, (f) the child was embarrassed to have old and poor mother , (g) the mother was sad and disappointed at her child, (h) the mother prayed to God, (i) the God granted the mother’s prayer, (j) the child realized his/her mistake, and (k) the child is punished by God as a rock; (2) the function of Malay folklore in maintaining integrity of ASEAN society are (a) assisting the education of young people, (b) increasing the feeling of group solidarity, and (c) giving social sanction that people have to well behave; and (3) the educational values developed from Malin Kundang and the versions are (a) the Malay society should be obedient to the parents, (b) the Malay societyshould not be haughty, and (c) Malay community should be accept the God’s decision.